2016
DOI: 10.1111/btp.12368
|View full text |Cite
|
Sign up to set email alerts
|

Florivory and floral larceny by fly larvae decrease nectar availability and hummingbird foraging visits at Heliconia (Heliconiaceae) flowers

Abstract: Insect larvae inhabit the corolla tubes of some Heliconia species (Heliconiaceae). In this study, we present the first evidence of the influence of these larvae on the pollination ecology of Heliconia plants. We provide experimental evidence that the flowers of Heliconia spathocircinata infested by flies have less nectar for pollinators and received fewer visits by hummingbird pollinators, in comparison with uninfested flowers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 27 publications
0
19
1
1
Order By: Relevance
“…Although hummingbirds prefer ornitophilous species, they act as generalist visitors depending on the ecological context (Dalsgaard et al . ) and may be very sensitive to plant resources ( e.g., avoiding flowers with high nectar‐robbing levels; Irwin & Brody , Missagia & Alves ). Indeed, hummingbirds appear to be less specialized and to visit more non‐ornitophilous plants in dry, seasonal, and open habitats (Arizmendi & Ornelas , Dalsgaard et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although hummingbirds prefer ornitophilous species, they act as generalist visitors depending on the ecological context (Dalsgaard et al . ) and may be very sensitive to plant resources ( e.g., avoiding flowers with high nectar‐robbing levels; Irwin & Brody , Missagia & Alves ). Indeed, hummingbirds appear to be less specialized and to visit more non‐ornitophilous plants in dry, seasonal, and open habitats (Arizmendi & Ornelas , Dalsgaard et al .…”
Section: Discussionmentioning
confidence: 99%
“…() found that nectar‐robbers indirectly affect female fitness of the hummingbird‐pollinated Ipomopsis aggregata via changes in pollination success as robbing itself did not reduce fruit and seed production in hand‐pollinated flowers. In a recent study in the Atlantic forest in Brazil, Missagia and Alves () reported that dipteran larvae‐infected flowers of Heliconia spathocircinata received fewer visits by hummingbird pollinators than uninfected flowers. Either way, we here not only demonstrate that offspring production is significantly reduced by a high incidence of floral antagonists, but also that this process exerts negative selective pressures on floral attractiveness traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Floral antagonists also alter flower traits. Florivory changes floral symmetry (McCall, 2008), volatile emissions (Lucas-Barbosa et al, 2011), nectar guides (Botto-Mahan and Ojeda-Camacho, 2000), rewards (Krupnick et al, 1999;Missagia and Alves, 2017), display size (Ashman and Penet, 2007;Liao et al, 2013), and resistance traits (McCall, 2006;Kaczorowski et al, 2014;Boyer et al, 2016), all of which could affect the preference of other floral antagonists or mutualists (e.g., Soper Gorden and . For example, florivory in Pedicularis gruina reduces the number of pollinator visits (Liao et al, 2013), further supporting the need to study interactions in a community context.…”
mentioning
confidence: 99%